The Design and Sustainability of Renewable Energy Incentives : An Economic Analysis - Meier, Peter; Vagliasindi, Maria; Imran, Mudassar; Eberhard, Anton; Siyambalapitiya, Tilak (Washington, DC: World Bank, 2014)
Rapid urbanization and economic growth, new demographic trends, and climate change are key challenges that developing countries must face as they strive to meet growing energy demand. The main objectives of this study are to offer: (a) a global taxonomy of the economic and financial incentives provided by renewable support schemes and (b) an economic modeling of the sustainability and affordability of such support schemes. In an attempt to contribute to the lively debate, this study provides a global taxonomy of the economic and financial incentives provided by renewable energy (RE) support schemes. It summarizes economic models of the sustainability and affordability of such support schemes, alongside operational advice on how the regulatory design may need to be modified to minimize the impact on the budget and be affordable to the poor, as well as how to identify and fill the financing gap. This analytical framework: (a) differentiates and illustrates tradeoffs among local, regional, and national impacts, in the short and long run; (b) captures distributional impacts (since subsidies to cover the incremental costs of RE may have very different beneficiaries); and (c) captures externalities and compares (where possible) alternative projects based on equivalent output and cost (comparing, for example, RE and energy efficiency projects against those using fossil fuels). The report is organized as follows: chapter one gives introduction. Chapter two presents the analytical framework that underpins the case studies, and provides the background for the principal research hypothesis of this report, which is better attention to the principles of economic analysis and market efficiency leads to more sustainable and effective policies. Chapter s three to ten present country case studies for Vietnam, Indonesia, Sri Lanka, South Africa, Tanzania, Egypt, Brazil, and Turkey. The conclusions of the study are presented in chapter eleven.